TQM DAN SUSTAINABILITY: KUALITAS YANG MENDUKUNG TUJUAN PEMBANGUNAN BERKELANJUTAN - Ramadhan, Fahmi Indra; Athallah, Muhammad Fakhri; Putra, Muhammad Aditya; Yusnaini, Yusnaini (Cahaya Ilmu Bangsa, 2025)
Significant changes in technology, social, political, and environmental conditions drive organizations to innovate to remain competitive while meeting sustainability demands. This study examines the impact of Total Quality Management (TQM) implementation on achieving corporate sustainability through a Systematic Literature Review (SLR) approach. Researchers identified relevant studies from various sources, such as Science Direct, Emeral, and Research Gate, to map key findings. Analysis of 33 journal articles shows that TQM positively contributes to three dimensions of sustainability (economic, social, and environmental) by reducing waste, optimizing resource use, and strengthening commitment to the Sustainable Development Goals (SDGs). However, TQM implementation is not free from challenges, such as organizational resistance, high investment requirements, and regulatory uncertainty. By understanding these dynamics, companies can develop strategies that integrate TQM as a foundation to strengthen competitiveness while contributing to sustainable global development.